Estudio de factores de riesgo asociados a la infección por Mycoplasma suis - Pereyra, N.B. (2010)
The objective of this study was to estimate the distribution of Mycoplasma suis infection in pig populations of Argentina and identify associated risk factors. Blood samples were collected from 284 pigs, including different productive categories of animals, in abattoirs and herds from Santa Fe, Córdoba and Buenos Aires provinces. Based on the polymerase chain reaction (PCR) amplification of the M. suis 16S rRNA gene, it was estimated a proportion of infected animals of 0.64. Non statistically significant (P>0.1) associations were found between gender, anemia herd history, and breeding conditions with PCR results. On the other hand, significant associations (P<0.1) were found between sanitary status to the infection and geographic origin and productive categories. It was estimated that pigs from Buenos Aires and Córdoba provinces were at higher risk of being PCR positive than pigs from Santa Fe, while piglets and post-weaning pigs were at lower risk of being PCR-positive than other categories. This study suggests that M. suis infection is widespread in the studied pig populations of Argentina.\n